Analysis of protease activity of enzyme isolated from compost soil - Valsange, Anmol; Evarkar, Sarang P; Tawde, Sachin V; Kareppa, Basawraj M; Gujar, Rekha S (International Multidisciplinary Research Journal, 2012)
Bacteria are very good source of enzymes as compared to animal or plant source and even synthetic enzymes. In the present investigation the protease activity has been analyzed. The source of enzyme i.e. protease producers were isolated from compost soil sample viz. collected from the Wanker farm field, Solapur. The protease producers were isolated, screened and grown on a suitable growth medium to obtain maximum production of enzyme. After production the crude enzyme is purified. The purified enzyme is analysed for its keratinolytic activity by using feathers.